2007
DOI: 10.4161/cc.6.1.3700
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin and Biliverdin Treatment of Atherosclerotic Diseases

Abstract: We have recently shown that the natural bile pigment bilirubin has antiproliferative effects on vascular smooth muscle cells (VSMCs). Bilirubin is the end product of heme catabolism mediated by heme oxygenases and has for decades been considered a toxic waste product of our bodies. However, 14 separate studies and a meta-analysis have documented an inverse correlation between atherosclerosis and the levels of bilirubin in normal individuals. Having high normal or supranormal levels of bilirubin is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 32 publications
4
69
0
1
Order By: Relevance
“…Direct evidence for the role of CO in vascular response was presented when it was shown that a reduction in CO generation resulted in increased vascular resistance in rat liver (Suematsu et al, 1994). Subsequent studies have clearly shown that HO-1-derived CO and bilirubin result in a vasorelaxant effect not only via cGMP-dependent but also via cGMP-independent (Ollinger et al, 2007;Li et al, 2008) stimulation of certain K channels Wang et al, , 2001Dong et al, 2007) and an increase in adiponectin levels (L'Abbate et al., 2007). Furthermore, it is considered unlikely that CO and NO represent redundant messenger molecules, even though both are active in the vessel wall.…”
Section: Carbon Monoxide Production Ho-dependent Ho-independentmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct evidence for the role of CO in vascular response was presented when it was shown that a reduction in CO generation resulted in increased vascular resistance in rat liver (Suematsu et al, 1994). Subsequent studies have clearly shown that HO-1-derived CO and bilirubin result in a vasorelaxant effect not only via cGMP-dependent but also via cGMP-independent (Ollinger et al, 2007;Li et al, 2008) stimulation of certain K channels Wang et al, , 2001Dong et al, 2007) and an increase in adiponectin levels (L'Abbate et al., 2007). Furthermore, it is considered unlikely that CO and NO represent redundant messenger molecules, even though both are active in the vessel wall.…”
Section: Carbon Monoxide Production Ho-dependent Ho-independentmentioning
confidence: 99%
“…Wang and associates (Cannon, 1929;Wang andWu, 1997, 2003;Wang, 1998;Ollinger et al, 2007;Li et al, 2008) have presented a series of elegant papers showing that CO-mediated relaxation was partially blocked by inhibitors of BK Ca channels without affecting Ca homeostasis. Other investigators have shown that CO and CO-releasing molecule (CORM)-3 stimulate BK Ca channels in HEK-293 cells Xi et al, 2004).…”
Section: Carbon Monoxide Production Ho-dependent Ho-independentmentioning
confidence: 99%
“…PPAR␥ agonists are shown to induce both HO-1 (21) and the rate-limiting chaperone protein EroL (46,47). PPAR␥ agonist that increases adiponectin may do so by increasing the levels of EroL chaperone protein (46).…”
Section: Decreasing Omentioning
confidence: 99%
“…PPAR␥ agonists are shown to induce both HO-1 (21) and the rate-limiting chaperone protein EroL (46,47). PPAR␥ agonist that increases adiponectin may do so by increasing the levels of EroL chaperone protein (46). Because PPAR␥ also increases HO-1 protein levels (21) and HO-1 is known as a chaperone protein, it is possible that one of the mechanisms by which HO-1 can increase adiponectin levels is through more efficient adiponectin stabilization and protection.…”
Section: Decreasing Omentioning
confidence: 99%
“…A CO és NO együttes vazorelaxáns hatása a sGC és cGMP útvonalakon keresztül érvényesül. A CO vazodilatív hatása a cGMP útvonalon kívül a kalcium-aktivált kálium csatornák (BKCa) aktiválásával is megvalósulhat [47,48]. Az antioxidáns és vazoaktív hatások mellett a HO-1-nek szerepe van az angiogenezisben és proliferációban is, valamint gyulladáscsökkentő és antiapoptotikus hatással is bír.…”
Section: Nem Genomiális Szignalizáció a Kardiovaszkuláris Rendszerbenunclassified